Method for the isolation of Escherichia coli K-12 mutants deficient in essential genes. - Armstrong, K A (1976)
We developed a general procedure for the induction and identification of mutations in chromosomal essential genes that are located in a diploid region of Escherichia coli K-12. The partial diploidy is conferred by an episome that is temperature sensitive for replication so that a mutant strain will form microcolonies at 42 C on complete media if an essential chromosomal gene in the diploid region is defective. Mutations identified by this procedure can be classified into cistrons by a complementation method devised for the purpose. To verify that the procedure works in practice, we fused an episome covering the rif region with an Ftslac+ and used the resulting temperature-sensitive episome to identify chromosomal mutations in essential functions near rif. As expected, a certain proportion of the mutations were in the rif gene, an essential gene that codes for the beta subunit of ribonucleic acid polymerase.